Molecular mechanisms mediating the neuroprotective role of the selective estrogen receptor modulator, bazedoxifene, in acute ischemic stroke: A comparative study with 17β-estradiol. Issue 171 (July 2017) - Jover-Mengual, Teresa; Castelló-Ruiz, María; Burguete, María C.; Jorques, María; López-Morales, Mikahela A.; Aliena-Valero, Alicia; Jurado-Rodríguez, Andrés; Pérez, Salvador; Centeno, José M.; Miranda, Francisco J.; Alborch, Enrique; Torregrosa, Germán; et al.
Highlights: Bazedoxifene is a "selective estrogen receptor modulator" approved for the treatment of postmenopausal osteoporosis. We have previously demonstrated that bazedoxifene protects the brain in a rat model of acute ischemic stroke. The current study shows that bazedoxifene inhibits apoptotic cell death in our experimental stroke model. Bazedoxifene modulates the expression of both estrogen receptor α and β, as well as the downstream MAPK/ERK1/2 signaling pathway. Our results lend mechanistic support to the consideration of bazedoxifene as a potential neuroprotective drug in acute ischemic stroke. Abstract: As the knowledge on the estrogenic system in the brain grows, the possibilities to modulate it in order to afford further neuroprotection in brain damaging disorders so do it. We have previously demonstrated the ability of the selective estrogen receptor modulator, bazedoxifene (BZA), to reduce experimental ischemic brain damage. The present study has been designed to gain insight into the molecular mechanisms involved in such a neuroprotective action by investigating: 1) stroke-induced apoptotic cell death; 2) expression of estrogen receptors (ER) ERα, ERβ and the G-protein coupled estrogen receptor (GPER); and 3) modulation of MAPK/ERK1/2 and PI3K/Akt signaling pathways. For comparison, a parallel study was done with 17β-estradiol (E2)-treated animals. Male Wistar rats subject to transient right middle cerebral artery occlusion (tMCAO, intraluminal thread technique, 60 min), were distributed in vehicle-, BZA- (20.7 ± 2.1 ng/mL in plasma) and E2- (45.6 ± 7.8 pg/mL in plasma) treated groups. At 24 h from the onset of tMCAO, RT-PCR, Western blot and histochemical analysis were performed on brain tissue samples. Ischemia-reperfusion per se increased apoptosis as assessed by both caspase-3 activity and TUNEL-positive cell counts, which were reversed by both BZA and E2. ERα and ERβ expression, but not that of GPER, was reduced by the ischemic insult. BZA and E2 had different effects: while BZA increased both ERα and ERβ expression, E2 increased ERα expression but did not change that of ERβ. Both MAPK/ERK1/2 and PI3K/Akt pathways were stimulated under ischemic conditions. While BZA strongly reduced the increased p-ERK1/2 levels, E2 did not. Neither BZA nor E2 modified ischemia-induced increase in p-Akt levels. These results show that modulation of ERα and ERβ expression, as well as of the ERK1/2 signaling pathway accounts, at least in part, for the inhibitory effect of BZA on the stroke-induced apoptotic cell death. This lends mechanistic support to the consideration of BZA as a potential neuroprotective drug in acute ischemic stroke treatment.